Investigation of the Mechanical and Thermal Properties of Waste Toner Powder Reinforced Polyester Composite for Industrial Applications - Chinemeogo C. OZIOKO; Ikechukwu C.-E. IKE-EZE; Nnanyelugo O. EDWIN; Dimelu K. EBUBE; Charles MBOHWA (FUDMA Journal of Engineering and Technology, 2025)
This experimental study explores the mechanical, thermal and morphological (SEM), properties of waste toner powder reinforced polyester composite, with an emphasis on its applicability in industrial settings. The research investigates the potential of waste toner powder, an abundant industrial by product, as a reinforcing agent in polyester composites which was made using the hand lay-up method. 5, 10, 15, 20, 25, 30, and 35 weight percent of waste toner loading were used to create the composite. The results of the tensile, flexural, impact, and hardness tests were compared for waste toner/polyester composites and unsaturated polyester with varying weight % loading. The results showed better enhancement in mechanical properties at 15wt. % of waste toner reinforcement. TGA and DTA was also observed to have 15% loading possessing better thermal stability than others. Morphological features of the composites were scrutinized using SEM. The results provide important new information about using waste toner powder as an economical and sustainable filler in polyester composites. presenting promising avenues for a diverse array of industrial applications.